DOMESTIC FIRMS’ RESPONSES TO INSTITUTIONAL CHANGES : A Case Study of Globalization and Local Competition in Vietnam - Dinh, Tuan (fi=Turun yliopisto|en=University of Turku|, 2018)
The globalization and MNEs’ penetration have been causing significant impacts on the institutional environment in emerging markets. Foreign MNEs invest in the host countries and create some positive impacts. They create more jobs and reduce the unemployment. MNEs also contribute significantly to the host countries’ GDP. As consequences, the local citizen’s living standard also increases. However, every coin has two sides. Globalization also brings some challenging threats to the domestic firms. The MNEs’ penetration causes some changes in the institutional environments. The competition in host countries also becomes more intense. Real-life experiences demonstrate that some domestic firms succeed in exploiting opportunities and overcoming challenges of globalization. However, not all companies have positive experiences. Some struggle for survival, while some are taken over by large MNCs. The object of this study was to examine the impact of institutional changes to the domestic firms’ response. The empirical stage of this research was guided by a theoretical framework developed from the theory in institution and strategic management. the framework guided the study to find the answer for the This study adopted the single case study with the aim to provide the in-depth insight to the research phenomenon. The case company was a Vietnamese enterprise which operated in the footwear industry. The results of the research show that there are different approaches that the firm may apply in their response. In this study, the penetration of MNEs caused some significant change in the institutional changes. When those changes happened, the case company perceived and anticipated the consequences of change in the local institution. Then they proactively made their strategic response based on their analysis and planning. However, the findings showed that the proactiveness of the strategic response was different regarding the target and context. The case company was proactive in their internationalized business but quite inactive in domestic activities. A critical finding from this study is to adapt effectively to the changes. Domestic firms need to keep their flexibility in strategic making process so that they can adapt quickly to the highly turbulent environment. Findings from this study contribute to the extent of institutional theory and strategic management. Moreover, this study also contributes some managerial implications by illustrating an example of how domestic firms successfully responded to institutional changes.